Participation of students with disabilities in higher education internationalisation activities - Karvelienė, Regina (Special Education, 2016)
The article analyses participation of students with disabilities in higher education internationalisation activities. In the course of research we tried to disclose theoretical links between higher education internationalisation concept and globalisation process, to analyse the experience of students with disabilities participating in internationalisation activities: the main factors that stimulate or restrict students from participation in international activities in higher education institutions. In order to implement the aim of the research, the theories of social participation and empowerment were referred to. Descriptive research method was applied to collect and analyse the data. The participants of the research – students with disabilities studying at Lithuanian state universities (N = 145). While analysing research data, the main factors that determined students’ decision to get involved in internationalisation activities at the university were indicated: the ambition to acquire deeper knowledge at international level in a particular study programme; the desire to ensure added value to future career; the pursuit to improve the knowledge of a foreign language. The main indicated factors that prevent students from participation in higher education internationalisation activities are as follows: the disability itself or special needs, low self-confidence and health problems.